Analysis of Factors Affecting Consumer's Decision in Choosing the Digital Fund Wallet - Heny Herawati (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2021)
This study aims to determine the effect of price, reference groups, and security on consumer decisions in choosing digital fund wallets on three campuses in Jakarta. This study used a sample of 100 respondents and the sampling technique used a simple random sampling technique. The data collection technique used a questionnaire of 43 question items which were assessed on a Likert scale of 1-5 and tested for validity and reliability. The analytical method use, regression analysis, correlation, the test of the coefficient of determination (R2), and t-test. Based on the regression analysis at a significant level of 5%, it shows (1) there is a positive and significant effect of price on consumer decisions in choosing a digital fund wallet, with a rx1y correlation of 0.678; the coefficient of determination R2x1y of 0.460; and sig value 0.000 < 0.05; (2) there is a positive and significant influence of the reference group on consumer decisions in choosing a digital fund wallet, with a rx2y correlation of 0.607; the coefficient of determination R2x2y is 0.368; and sig value 0.000 <0.05; (3) there is a positive and significant security effect on consumer decisions in choosing a digital fund wallet, with a rx3y correlation of 0.746; the coefficient of determination R2x3y of 0.556; and sig value 0.000 < 0.05.